Analysis of Student Hearings Towards a Proposal in radio programming - Rodríguez-Solís, Luz del Alba (Universidad Autónoma de Tamaulipas, 2010)
In Latin America have done extensive research on media consumption among adolescents, some researchers have observed the phenomenon from the apathy toward the content and consumption resulting from self-expression. But investigations have also made some proposals: are apathetic young people to the contents or the contents are those that produce their apathy?, Does his attitude is a reflection of the environment that has forgotten them, structuring and designing programs after the event to reflect not interested? Have you made especially radio to offer what other electronic means if they are offered? This paper analyzes patterns of consumption, use and value of this audience, in order to identify whether it is necessary to develop program proposals in line with their expectations.